2002
DOI: 10.1126/science.1073681
|View full text |Cite
|
Sign up to set email alerts
|

White Collar-1, a Circadian Blue Light Photoreceptor, Binding to the frequency Promoter

Abstract: In the fungus Neurospora crassa, the blue light photoreceptor(s) and signaling pathway(s) have not been identified. We examined light signaling by exploiting the light sensitivity of the Neurospora biological clock, specifically the rapid induction by light of the clock component frequency (frq). Light induction of frq is transcriptionally controlled and requires two cis-acting elements (LREs) in the frq promoter. Both LREs are bound by a White Collar-1 (WC-1)/White Collar-2 (WC-2)-containing complex (WCC), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
619
2
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 497 publications
(666 citation statements)
references
References 33 publications
22
619
2
5
Order By: Relevance
“…Both BLR and WC proteins contain conserved Per-ARNT-Sim (PAS) domains, which have been shown to be involved in signal transduction through monitoring of the energy state of the cell, in protein-protein interactions and in the sensing of environmental signals (Möglich et al, 2009;Taylor & Zhulin 1999). In N. crassa, WC-1 and WC-2 (White Collar 1 and White Collar 2) mediate all known light responses (Ballario et al, 1996;Cheng et al, 2003;Degli-Innocenti & Russo, 1984;Froehlich et al, 2002;Harding & Turner, 1981;He et al, 2002;Herrera-Estrella & Horwitz, 2007;Linden & Macino, 1997). However, in T. atroviride, there appear to be both BLR-dependent and -independent blue-light perception pathways (Berrocal-Tito et al, 2000;CasasFlores et al, 2006;Rocha-Ramirez et al, 2002;Schmoll et al, 2010).…”
Section: Blr-1 and Blr-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Both BLR and WC proteins contain conserved Per-ARNT-Sim (PAS) domains, which have been shown to be involved in signal transduction through monitoring of the energy state of the cell, in protein-protein interactions and in the sensing of environmental signals (Möglich et al, 2009;Taylor & Zhulin 1999). In N. crassa, WC-1 and WC-2 (White Collar 1 and White Collar 2) mediate all known light responses (Ballario et al, 1996;Cheng et al, 2003;Degli-Innocenti & Russo, 1984;Froehlich et al, 2002;Harding & Turner, 1981;He et al, 2002;Herrera-Estrella & Horwitz, 2007;Linden & Macino, 1997). However, in T. atroviride, there appear to be both BLR-dependent and -independent blue-light perception pathways (Berrocal-Tito et al, 2000;CasasFlores et al, 2006;Rocha-Ramirez et al, 2002;Schmoll et al, 2010).…”
Section: Blr-1 and Blr-2mentioning
confidence: 99%
“…In N. crassa, light input to the circadian system is mediated by binding of the WC-1/WC-2 complex to the frq promoter at the consensus LREs (Froehlich et al, 2002;He & Liu, 2005). Endogenous rhythms associated with conidiation have been identified in some strains of T. atroviride and T. pleuroticola (Deitzer et al, 1988;Steyaert et al, 2010a).…”
Section: Regulation Of Circadian Rhythmsmentioning
confidence: 99%
“…WC proteins have been well characterized in the filamentous ascomycete Neurospora crassa (Ballario et al, 1996;Linden and Macino, 1997;Froehlich et al, 2002;He et al, 2002), and homologues have been identified in ascomycetes, basidiomycetes, and zygomycetes (for review, see Corrochano, 2007 (Idnurm and Heitman, 2005;Lu et al, 2005). WHITE COLLAR orthologues are also encoded in the genome of A. nidulans (Greene et al, 2003), and the corresponding gene products have recently been shown to influence light sensing, sexual development, and mycotoxin production (Purschwitz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…WC proteins have been well characterized in the filamentous ascomycete Neurospora crassa (Ballario et al, 1996;Linden and Macino, 1997;Froehlich et al, 2002;He et al, 2002), and homologues have been identified in ascomycetes, basidiomycetes, and zygomycetes (for review, see Corrochano, 2007). For example, Phycomyces blakesleeanus mutants defective in blue-light-dependent phototrophism may contain mutations in the madA gene, which encodes a protein similar to WC-1 of N. crassa (Idnurm et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…WC-1 and WC-2 form complexes through the interaction of the PAS-C domain of WC-1 and the PAS domain of WC-2 . These complexes bind to the light-response element (LRE) found in the promoters of light-regulated genes even in the dark (Froehlich et al, 2002;He & Liu, 2005;Káldi et al, 2006). In the WC-1 protein, a specialized PAS domain essential for blue/UVA light perception, called LOV (light, oxygen, voltage), that binds FAD, similar to the first LOV domains described in plant phototropins, has been identified (Froehlich et al, 2002;He et al, 2002).…”
Section: Introductionmentioning
confidence: 99%